PENGARUH PENERAPAN QUICK ON THE DRAW TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 15 PADANG - Prima Sari, Tika; Longgom. Nst, Minora; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTÂ Students understanding of mathematical concepts are still low in class XI Science SMAN 15 Padang become the background for this study. The study aims to determine whether the ability of the students understanding of mathematical concepts by applying quick on the draw better than the ability of the students understanding of mathematical concepts by applying conventional learning in class XI Science SMAN 15 Padang. This study is a randomized study design experiments to sabjek. Analysis of the data using one-way t test with MINITAB program. Based on the analysis of data obtained P-value = 0.008 means less than Î± = 0.05 level, so it can be concluded that the ability of understanding mathematical concepts students with a quick on the draw better than the ability of the students understanding of mathematical concepts by applying conventional teaching students of class XI Science 15 Padang.